2016
DOI: 10.1093/mnras/stv2865
|View full text |Cite
|
Sign up to set email alerts
|

The transverse velocity of the Andromeda system, derived from the M31 satellite population

Abstract: We present a dynamical measurement of the tangential motion of the Andromeda system, the ensemble consisting of the Andromeda Galaxy (M31) and its satellites. The system is modelled as a structure with cosmologically-motivated velocity dispersion and density profiles, and we show that our method works well when tested using the most massive substructures in high-resolution Λ Cold Dark Matter (ΛCDM) simulations. Applied to the sample of 40 currently-known galaxies of this system, we find a value for the transve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 40 publications
4
52
2
Order By: Relevance
“…The choice of the LG model and the CF2 constraint allows us to study the way the structure of the LG and the nearby universe affects our knowledge of masses of the MW and M31. A particular emphasis has been placed also on the effects of using a low-vtan estimate (the value found by Sohn et al (2012), referred to as v (I) tan ) and a high one (v (II) tan , derived by Salomon et al (2016)). We applied these models to objects drawn from two different types of simulations: a series of constrained simulations (CS), from which it was possible to gather halo pairs living in a large scale environment akin to the observational one, and a standard, random ΛCDM (Rand).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the LG model and the CF2 constraint allows us to study the way the structure of the LG and the nearby universe affects our knowledge of masses of the MW and M31. A particular emphasis has been placed also on the effects of using a low-vtan estimate (the value found by Sohn et al (2012), referred to as v (I) tan ) and a high one (v (II) tan , derived by Salomon et al (2016)). We applied these models to objects drawn from two different types of simulations: a series of constrained simulations (CS), from which it was possible to gather halo pairs living in a large scale environment akin to the observational one, and a standard, random ΛCDM (Rand).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the latter, in fact, there is yet no clear consensus on its real value, for which currently two incompatible estimates exist. These were obtained using different techniques: the one of Sohn et al (2012), who found vtan= 17 ± 17 (referred to as v (I) tan ) directly measuring the motion stellar population within M31 against background galaxies; and the one of Salomon et al (2016), who inferred vtan=164 ± 62 (referred to as v (II) tan ) using precise satellite galaxies data of the PAndAS survey (McConnachie et al 2009;Martin et al 2013a,b).…”
Section: The Local Group Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, even the tangential velocity of M31 is very uncertain. Two recent measurements give very different, inconsistent results: a value of 17 km s −1 from Sohn et al (2012) and 164 km s −1 by Salomon et al (2016). For And II the tangential velocity is completely unknown.…”
Section: Observational Test Of the Modelmentioning
confidence: 95%
“…The common orbital history of these galaxies has been repeatedly studied in the past in response to improvements in the measurement of their PM (e.g. van der Marel et al 2012b;Salomon et al 2016;Patel et al 2017;Semczuk et al 2018). Most recently, van der Marel et al (2019) have explored the implications of the new Gaia DR2 PM for these galaxies.…”
Section: Preliminariesmentioning
confidence: 99%